Sustainability in a building: from development -as a socioeconomic category- to sustainable construction: Sustainability in a building: from development —as a socioeconomic category— to sustainable construction - Zuleta Roa, Gloria (Corporación Universitaria del Caribe, CECAR., 2019)
Reflection article that presents the historical evolution of the concept of sustainability, in relation to the construction of the human habitat. From its origins, linked to development issues, to changes, and socio-economic and cultural problems; and its application in different global and local areas. Even its intimate relationship with the human condition, in the permanent struggle between a predatory culture —originated by the desire for permanent consumption— and the culture of care and conservation, aimed at protecting life. A discussion on three categories is proposed: development, sustainable development and sustainable construction.